A 3-D functional–structural grapevine model that couples the dynamics of water transport with leaf gas exchange. (23rd December 2017) - Zhu, Junqi; Dai, Zhanwu; Vivin, Philippe; Gambetta, Gregory A; Henke, Michael; Peccoux, Anthony; Ollat, Nathalie; Delrot, Serge
Abstract: Background and Aims: Predicting both plant water status and leaf gas exchange under various environmental conditions is essential for anticipating the effects of climate change on plant growth and productivity. This study developed a functional–structural grapevine model which combines a mechanistic understanding of stomatal function and photosynthesis at the leaf level (i.e. extended Farqhuhar–von Caemmerer–Berry model) and the dynamics of water transport from soil to individual leaves (i.e. Tardieu–Davies model). Methods: The model included novel features that account for the effects of xylem embolism ( f PLC ) on leaf hydraulic conductance and residual stomatal conductance ( g 0 ), variable root and leaf hydraulic conductance, and the microclimate of individual organs. The model was calibrated with detailed datasets of leaf photosynthesis, leaf water potential, xylem sap abscisic acid (ABA) concentration and hourly whole-plant transpiration observed within a soil drying period, and validated with independent datasets of whole-plant transpiration under both well-watered and water-stressed conditions. Key Results: The model well captured the effects of radiation, temperature, CO2 and vapour pressure deficit on leaf photosynthesis, transpiration, stomatal conductance and leaf water potential, and correctly reproduced the diurnal pattern and decline of water flux within the soil drying period. In silico analyses revealed that decreases in g 0 with increasing f PLC were essential to avoid unrealistic drops in leaf water potential under severe water stress. Additionally, by varying the hydraulic conductance along the pathway (e.g. root and leaves) and changing the sensitivity of stomatal conductance to ABA and leaf water potential, the model can produce different water use behaviours (i.e. iso- and anisohydric). Conclusions: The robust performance of this model allows for modelling climate effects from individual plants to fields, and for modelling plants with complex, non-homogenous canopies. In addition, the model provides a basis for future modelling efforts aimed at describing the physiology and growth of individual organs in relation to water status.